Foetal and neonatal alloimmune thrombocytopenia – The role of the HLA-DRB3*01:01 allele for HPA-1a-immunisation and foetal/neonatal outcome. (February 2020) - Kjeldsen-Kragh, Jens; Ahlen, Maria Therese
Abstract: Foetal and neonatal alloimmune thrombocytopenia (FNAIT) is the platelet counterpart of haemolytic disease of the foetus and newborn. Among Caucasians, around 80 % of FNAIT cases and some of the most severe cases, are caused by alloantibodies against the human platelet antigen 1a (HPA-1a). For around 3 decades it has been known that almost all HPA-1a-immunised women are HLA-DRB3*01:01 positive. The HLA molecule encoded by the HLA-DRA/DRB3*01:01 genes seems to be of crucial importance for initiating the immune response against HPA-1a. The HLA-DRB3*01:01 carrier status is not only important as a risk factor for immunisation, but does also have a significant impact on foetal/neonatal outcome. The possible role of HLA-DRB3*01:01 typing as tool for risk stratification is discussed.